2008
DOI: 10.1007/s00431-008-0858-z
|View full text |Cite
|
Sign up to set email alerts
|

Noonan syndrome caused by germline KRAS mutation in Taiwan: report of two patients and a review of the literature

Abstract: Noonan syndrome is a highly variable disorder that has significant phenotypic overlap with Costello syndrome and cardio-facio-cutaneous syndrome. KRAS mutation was the second reported gene for Noonan syndrome. This study screened for mutation of the KRAS gene in 57 unrelated ethnic Chinese children suffering from Noonan syndrome without PTPN11 gene mutation in Taiwan. This work only identified two patients with different missense mutations (c.40G>A, p.Val14Ile; c.108A>G, p.Ile36Met) in the exon 1 of KRAS gene.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
18
1

Year Published

2010
2010
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 34 publications
(21 citation statements)
references
References 18 publications
2
18
1
Order By: Relevance
“…d [Carta et al, 2006;Ko et al, 2008;Lo et al, 2008;Schubbert et al, 2006;Zenker et al, 2007b]. The frequency of the manifestation in patients with the gene was significantly lower compared with that observed in RAF1-positive patients (Po0.05 by Fisher's exact test).…”
Section: Discussioncontrasting
confidence: 50%
See 1 more Smart Citation
“…d [Carta et al, 2006;Ko et al, 2008;Lo et al, 2008;Schubbert et al, 2006;Zenker et al, 2007b]. The frequency of the manifestation in patients with the gene was significantly lower compared with that observed in RAF1-positive patients (Po0.05 by Fisher's exact test).…”
Section: Discussioncontrasting
confidence: 50%
“…To highlight the clinical pictures of patients with RAF1 mutations, clinical manifestations in 52 patients with RAF1 mutations [Ko et al, 2008;Pandit et al, 2007;Razzaque et al, 2007], 172 patients with PTPN11 mutations [Jongmans et al, 2005;Musante et al, 2003;Tartaglia et al, 2002;Zenker et al, 2004], 73 patients with SOS1 mutations [Ferrero et al, 2008;Narumi et al, 2008;Roberts et al, 2007;Tartaglia et al, 2007;Zenker et al, 2007a] and 18 patients with KRAS mutations [Carta et al, 2006;Ko et al, 2008;Lo et al, 2008;Schubbert et al, 2006;Zenker et al, 2007b] are summarized in Table 3. The frequency of perinatal abnormalities was similar between patients with RAF1 and SOS1.…”
Section: Discussionmentioning
confidence: 99%
“…80,82,84-86 Early studies suggested patients with KRAS mutations are more severely medically and cognitively affected than most patients with Noonan syndrome (table 2). 80 In 2009, Kratz and colleagues 87 reported the unusual feature of craniosynostosis and a missense KRAS mutation in two unrelated patients with Noonan syndrome.…”
Section: Diagnosismentioning
confidence: 99%
“…80 In 2009, Kratz and colleagues 87 reported the unusual feature of craniosynostosis and a missense KRAS mutation in two unrelated patients with Noonan syndrome. 87 85% of patients with Noonan syndrome who have KRAS mutations have cardiac involvement, 84 and all have mild-to-moderate intellectual disability. 86 …”
Section: Diagnosismentioning
confidence: 99%
“…These mutations confer milder gain-of-function effects than somatically acquired cancerassociated mutations (9). Replacement of the valine residue located at position 14 by isoleucine is one of the most frequent KRAS mutations (10). Although this mutation is adjacent to amino acid residues typically altered in cancer, KRAS V14I displays an intermediate intrinsic GTPase activity compared with wild-type and oncogenic isoforms (9).…”
mentioning
confidence: 99%